2018
DOI: 10.1101/360966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Named-Entity Recognition approaches in plant molecular biology

Abstract: Abstract. Text mining research is becoming an important topic in biology with the aim to extract biological entities from scientific papers in order to extend the biological knowledge. However, few thorough studies on text mining and applications are developed for plant molecular biology data, especially rice, thus resulting a lack of datasets available to train models able to detect entities such as genes, proteins and phenotypic traits. Since there is rare benchmarks for rice, we have to face various difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Conditional Random Fields (CFR) [33] are one of the most widely used generative classifiers intended to address NER tasks [61,62,63] as long as their focus is on sequential data. To predict named entity tags, a word-level examination is conducted with a set of sorted and sequential words mapped with an internal state of transitions produced by their corresponding entity tags.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Conditional Random Fields (CFR) [33] are one of the most widely used generative classifiers intended to address NER tasks [61,62,63] as long as their focus is on sequential data. To predict named entity tags, a word-level examination is conducted with a set of sorted and sequential words mapped with an internal state of transitions produced by their corresponding entity tags.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…The proposed model uses a hybrid neural network technique BiLSTM-CRF (bidirectional long short term memory -Conditional Random Field) and provides better performance than baseline models. Similarly, Do et al [18] has also proposed a hybrid NER technique for the identification of named entities in plant molecular biology dataset. The proposed technique identifies genes, proteins and phenotypic Traits as named-entities.…”
Section: Named Entity Recognition Techniquesmentioning
confidence: 99%
“…However, Etaiwi et al [23] proposed a model for the identifi cation of Arabic Names and states that the CRF is very effi cient in identifying NER problem. However, the recent studies [16,18,32] concluded that the use of CRF alone will not give a better performance. The amalgamation of CRF and neural networks will provide effi cient performance.…”
Section: Maim Training and Aspect Identifi Cation Phasementioning
confidence: 99%
See 1 more Smart Citation
“…By sharing this dataset on the PubAnnotation platform and be available at the BioNLP Open Shared Tasks (BioNLP-OST, https://2019.bionlp-ost.org), we invited participants to implement their own methods to solve NER tasks for this dataset. Furthermore, to evaluate the performances, we compared their approaches, implemented during the task, with our method [6], implemented before the hackathon.…”
Section: Objectivementioning
confidence: 99%